Sosialisasi Tangguh Bencana Banjir Di Desa Sungai Tabuk, Kecamatan Simpang Empat, Kabupaten Banjar, Provinsi Kalimantan Selatan - Andi Tenri Sompa; Yuanita Setyastuti; Yayan Daryanto; Akhmad Piqi Adum Damara; I Gede Kariada; Ilhamuddin; Lisa Yuliana; Maira Ulfah; Raudatul Jannah; Ratih Andriani (Wadah Inovasi Indonesia, 2021)
At the beginning of the year, high rainfall triggered overflows of river water which, in flooding, one of which was in Sungai Tabuk Village, Simpang Empat District, Banjar Regency. The purpose of this service is to provide knowledge about potential disasters, characteristics, impacts, and cycles of flood disaster management for the village government and the people of Sungai Tabuk Village. The methodology used to provide understanding and increase awareness and improve communication between communities is through the Socialization of Flood Disaster Resilient. From this activity, it will increase public understanding and awareness to know the threat of disasters in their area so that they are able to organize and reduce disaster risk to reduce vulnerability to disasters with preparedness and make efforts to prevent and recover post-floods.